Kerjasama Guru dan Orang Tua dalam Pembentukan Karakter Disiplin Siswa Kelas V SDN 190 Pekanbaru - Rhenalda Elpa; Febrina Dafit (Civiliza Publishing, 2022)
The study aims to describe the form, supporting factors and inhibiting factors of teacher and parent cooperation in the formation of disciplined character. The approach used is a descriptive approach. Sources of data involved 1 teacher and 3 parent with research instrument used were observation guidelines, interview guidelines, documentation guidelines. The data validity technique uses triangulation. This data analysis technique uses themiles and huberman model, namely data reduction, data presentation, and conclusion. The results of this study indicate that the forms of cooperation between teachers and parents include: Forming associations, conducting sicialization of disciplined character education, programs for parents, involving parents in planning disciplined, character education, making agreements about disciplined, making agreements tocombat the impact of media use on students, teachers visit to parents homes. The supporting factors for the cooperation of teachers and parents are the facilities and infrastructure and the involvement of parents. The inhibiting factors are parental awareness, there are still parents who cannot attend meetings, communication between teachers and parents.